Explosion in the History of the Nobility in French Historiography: Recent Approaches and Methods - Figeac, Michel (Historical Studies on Central Europe, 2021)
For the past thirty years, the history of the nobility has been one of the fields of social history that have mobilized most researchers. This trend is largely due to the interest shown in new family collections, in correspondence and in private writings. We see this abundant mass of publications as being the reflection of the diversity of the nobility. A first block of authors have isolated noble categories: parliamentary nobility, “second” order nobility, poor nobility, etc. A second type of research has focused on personages emblematic of their milieus, and finally, some historians have been interested in comparisons with other European aristocracies. The second section of the article will show how the transformations of the monarchical state engendered mutations in the second order. Finally, it will be shown how scholarship on social changes has more particularly studied differences between town and country, material culture and mobility and noble culture.